2016
DOI: 10.1111/sed.12330
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional seismic characterization of a complex sediment drift in the South China Sea: Evidence for unsteady flow regime

Abstract: This study describes a previously unobserved reflection seismic configuration comprising a honeycomb planform and a repeated erosion/infill cross‐section, based on high‐resolution three‐dimensional/two‐dimensional seismic data and bathymetric data. The honeycomb structures cover an area of more than 5000 km2 and are developed within the Late Miocene to recent deep‐water sediments of the north‐western South China Sea. Linear erosional troughs up to 10 km long and 1 km wide are widely developed in this area, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…A similar kilometer-scale, seafloor HP was previously interpreted to originate from smaller counterparts developed in underlying sedimentary units as a result of a sediment drift depositional pattern (Sun et al, 2017). This pattern is characterized by wave-like geometries corresponding to cut-and-fill erosional features with honeycomb planforms.…”
Section: Page Of 27supporting
confidence: 60%
See 2 more Smart Citations
“…A similar kilometer-scale, seafloor HP was previously interpreted to originate from smaller counterparts developed in underlying sedimentary units as a result of a sediment drift depositional pattern (Sun et al, 2017). This pattern is characterized by wave-like geometries corresponding to cut-and-fill erosional features with honeycomb planforms.…”
Section: Page Of 27supporting
confidence: 60%
“…3A) carved into u1 (Fig. 4B, zoom2 and zoom3) are, however, deeper (~200-300 m) than those (~60 m) described by Sun et al (2017), suggesting that other important processes are involved.…”
Section: Page Of 27mentioning
confidence: 78%
See 1 more Smart Citation
“…Collectively, the sedimentation rates and the present-day geothermal gradient are both high in the Qiongdongnan Basin [38]. The thick sediment sequences, high geothermal gradient along with faulting and/or diapirism, have facilitated the generation and migration of the hydrocarbons in the basin [39]. The widely distributed bottom-simulating reflectors and gas chimneys identified in the Qiongdongnan Basin were linked to the accumulation of gas hydrate [40,41].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Zhu et al, 2009 16 ). Previous research has revealed contourite deposition (honeycomb structures) west of the Zhongjianbei platform 17 , and contourite channels around the Triton and Zhongjian platforms 18 20 .
Figure 2 (a) Multibeam bathymetric map; and b) Morphosedimentary interpretation including large features.
…”
Section: Regional Settingmentioning
confidence: 98%